The Impact of Artificial Intelligence on the Legal Field - Bo, Wang (International Conference on Fundamental and Applied Research (I-CFAR), 2026)
Artificial Intelligence (AI) has experienced exponential growth in recent decades, with its influence permeating various sectors, including the legal field. This study aims to systematically explore the multifaceted impacts of AI on legal practice, judicial decision- making, legal education, and related ethical-legal challenges. Adopting qualitative research methods, the study integrates literature review (covering 2018–2023 Chinese and English core journals and authoritative reports), case analysis (e.g., U.S. COMPAS bail algorithm, China’s Beijing Internet Court AI system), and data synthesis (from official sources like the Supreme People’s Court of China and the American Bar Association). Findings reveal that AI significantly enhances efficiency in legal retrieval (via NLP and machine learning), improves the accuracy of case analysis (through pattern recognition in historical cases), expands access to legal consultation (via intelligent chatbots), and innovates legal education (through VR/AR immersive learning). However, AI application also raises critical issues: algorithmic bias in judicial decisions, unclear legal status of AI entities, and potential displacement of legal practitioners. To address these challenges, the study proposes policy recommendations, including establishing AI judicial oversight mechanisms and formulating technology-neutral legal norms. This research contributes to bridging the gap between AI technological development and legal system adaptation, providing theoretical guidance for the sustainable integration of AI and law.